Use of Geothermal Waters of Azerbaijan for Neutralization of Organic Components of Solid Household Waste - Garaybeyli , S.A. (Herald of Azerbaijan Engineering Academy, 2024)
Possibilities of using geothermal waters of Azerbaijan for neutralizing the organic component of solid household waste from pathogenic microorganisms are being considered. Based on the conducted experiments, the dependence of the degree of solid waste neutralization on temperature, the degree of neutralization on the volume of empty salt solution, and the degree of neutralization of solid household waste on the temperature of thermal water containing 1% H2S was determined.